'ISIS is not Islam': Epistemic Injustice, Everyday Religion, and Young Muslims' Narrative Resistance. (23rd May 2020) - Sandberg, Sveinung; Colvin, Sarah
Abstract: Powerful narratives that invoke religious concepts— jihad, Sharia, shahid, Caliphate, kuffar, and al-Qiyāmah —have accompanied jihadi violence but also inspired robust counter-narratives from Muslims. Taking a narrative criminological approach, we explore the rejection of religious extremism that emerges in everyday interactions in a religious community under intense pressure in Western societies. Drawing on qualitative interviews with 90 young Muslims in Norway, we argue that young Muslims suffer epistemic injustice in their narrative exclusion from the mainstream and assess the narrative credibility they try to maintain in the face of marginalization. We suggest that young Muslims' religious narratives reject a mainstream characterization of Islam as essentially a religion of aggression and simultaneously join forces with that mainstream in seeking the narrative exclusion of the jihadi extremists.